FACTORS ASSOCIATED TO ALVEOLITIS IN PEOPLE OVER 18 YEARS OLD - Yudit Berrio Rey; María Elena Rey Ávila (Universidad de Ciencias Médicas de Villa Clara, 2013)
A number of 362 adults who suffered from alveolitis were studied through a descriptive and transversal study, which has as objective to describe the association of different factors with the apparition of dry and humid alveolitis in people over 18 years old; these patients received care in "Celia Sánchez Manduley" Clinic from December, 2007 to December, 2009.The deficient work of the stomatologist showed very significant differences between both types of alveolitis, and dry type predominated. A very significant association between the excessive use of anaesthesia and dry alveolitis was found, as well as, between the inappropriate manoeuvre of extraction and dry one. Smoking habit after extraction was associated significantly to dry alveolitis in patients with inadequate conducts, as well as, sun exposure after exodontic procedure and non fulfilment of pre and postoperative indications.